Hubungan Antara Frekuensi Bermain Game Online (Seperti Mobile Legends, PUBG & Free Fire) dengan Tingkat Stres pada Mahasiswa - Zulfa Harum Fasya; Hidayat Qodri Tarigan; Feby Deva Sabiya; Muhammad Wahyu Kurniawan; Najlatul Hulwa; Adelyna Oktavia Nasution (Lembaga Pengembangan Kinerja Dosen, 2025)
Online gaming has become an inseparable part of daily life, especially among students. Games such as Mobile Legends, PUBG, and Free Fire are not only used as a source of entertainment, but are also often used as a way to relax and relieve stress after a busy academic schedule. However, excessive use of online games can have negative effects on mental health, such as poor sleep quality, increased anxiety, and elevated stress levels. This study aims to determine whether there is a relationship between the frequency of online gaming and stress levels among students. The research was conducted with a quantitative approach using the Spearman correlation method. A total of 55 students participated as respondents by filling out a questionnaire that measured how often they play games and the stress levels they experience. The analysis results show a correlation coefficient of 0.177 with a p-value > 0.05, indicating that there is no significant relationship between the frequency of online gaming and stress levels among students. This study is expected to serve as an initial reference for students to be more mindful in managing their gaming time and maintaining their mental health.